Mesoporous pores impregnated with Au nanoparticles as effective dielectrics for enhancing triboelectric nanogenerator performance in harsh environments - Chun, Jinsung; Kim, Jin Woong; Jung, Woo-suk; Kang, Chong-Yun; Kim, Sang-Woo; Wang, Zhong Lin; Baik, Jeong Min (Royal Society of Chemistry, 2015)
A facile and scalable synthesis of mesoporous films impregnated with Au nanoparticles (NPs) as effective dielectrics is demonstrated for enhancing the nanogenerator performance based on vertical contact-separation mode. This technique is so simple and scalable, providing a promising solution for developing large-scale and practical self-powered devices. The spatial distribution of Au NPs made it possible to fabricate an Au NP-embedded mesoporous triboelectric nanogenerator (AMTENG) with a high output power of 13 mW under cycled compressive force, giving over 5-fold power enhancement, compared with a flat film-based TENG under the same mechanical force. It is proposed that the presence of aligned dipoles produced due to the charges created by the contact between Au NPs and PDMS inside the pores can influence the surface potential energy of mesoporous films. With such an enhanced power output and unique device design, we demonstrate various applications such as self-powered shape mapping sensors, foot-step driven large-scale AMTENGs, and integrated circuits with capacitors for powering commercial cell phones for realizing self-powered systems from footsteps, wind power, and ocean waves.
Keywords: HARVESTING BIOMECHANICAL ENERGY; CONTACT-ELECTRIFICATION; TRANSPARENT; VIBRATION; DRIVEN